2003
DOI: 10.1099/jmm.0.05122-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa alginate is refractory to Th1 immune response and impedes host immune clearance in a mouse model of acute lung infection

Abstract: Pseudomonas aeruginosa is an opportunistic respiratory pathogen that accounts for most of the morbidity and mortality in cystic fibrosis (CF) patients. In CF-affected lungs, the bacteria undergo conversion from a non-mucoid to a non-tractable mucoid phenotype, due to overproduction of alginate. The effect of alginate production on pathogenicity was investigated by using an acute lung infection mouse model that compared a non-mucoid P. aeruginosa strain, PAO1, to its constitutive alginate-overproducing derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 64 publications
2
61
0
1
Order By: Relevance
“…Alginate has been shown to protect P. aeruginosa against human leukocyte killing (11), in addition to inhibiting pulmonary clearing and increasing bacterial load in a mucine lung infection model (19). Psl expression is also important for reduced phagocytosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Alginate has been shown to protect P. aeruginosa against human leukocyte killing (11), in addition to inhibiting pulmonary clearing and increasing bacterial load in a mucine lung infection model (19). Psl expression is also important for reduced phagocytosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our microarray analysis showed FRD1-dependent up-regulation of genes with antiapoptotic effect on epithelial and other cell types (63)(64)(65), and exposure to an alginate-producing strain results in diminished apoptosis in Calu-3 airway epithelial cells. Thus, the lack of the appropriate host defense and inflammatory milieu in the airways, and impaired bacterial clearance because of reduced epithelial cell apoptosis (59,66), may explain the increased persistence of these strains in animal models of acute infection (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent intense neutrophil-dominated airway inflammation and progressive lung disease are major causes of morbidity and mortality in this disease (13,14). In vivo studies suggest that clearance of mucoid strains from murine lungs is diminished compared with nonmucoid strains, indicating improved survival of alginateproducing strains in the respiratory tract (15)(16)(17)(18). Alginate enhances mucin secretion by tracheal epithelial cells (19), and may inhibit neutrophil migration to the sites of infection (20).…”
mentioning
confidence: 99%
“…Interestingly, percent survival of PDO300 biofilm bacteria was similar to that seen with wild-type biofilms (PA01, PA14, and FRD1, see below), suggesting that the overproduction of alginate did not increase P. aeruginosa biofilm bacterial resistance to leukocyte killing. However, a recent work demonstrated that after 48 h of infection with this mutant strain, there was marked inflammation and high planktonic bacterial load in a variety of mouse organs vs the parent strain PA01 (46). Thus, the ability to overproduce alginate seems to have an early protective effect in acute infection models.…”
Section: Figurementioning
confidence: 99%